Ecophysiology of eucalyptus marginata and corymbia calophylla in decline in an urban parkland - Grigg, A.; Close, D.; Lambers, H.; Ruthrof, K.; Dixon, Kingsley (Blackwell Publishing Asia, 2009)
Eucalypt trees are in decline throughout urban landscapes of south western Australia. This study investigated the cause of decline in Eucalyptus marginata and Corymbia calophylla trees in parkland and compared water and nutrient relations with healthy trees in adjacent bushland in Perth, Western Australia. It was hypothesized that: (i) trees were drought stressed through competition for soil water by the vigorous turf; (ii) excessive uptake of nitrogen, because of fertilizer application to turf, caused toxicity; and/or (iii) micronutrient (Cu, Fe, Mn and/or Zn) deficit was induced by high-pH irrigation water applied to turf around parkland trees. Leaf water potential showed aseasonal variation in the irrigated parkland trees and foliar 13C indicated that parkland trees generally had low water-use efficiency and were not drought stressed relative to bushland trees. Foliar N levels were not significantly different between parkland and bushland trees indicating that excess N uptake was not a factor in the decline. Foliar total Fe, 'metabolically active' Fe, Cu and Zn concentrations were not significantly different between parkland and bushland trees. Foliar manganese concentrations were indicative of deficiency and significantly lower in parkland trees (5-14 g g-1) relative to bushland trees (22-35 g g-1). It is concluded that application of alkaline irrigation water to the parkland site reduced the plant-availability of Mn; however, our study of only one parkland site does not allow us to generalize the results across other parklands. © 2009 Ecological Society of Australia.